Investigating Associations between Subclinical Hypothyroidism and Pregnancy Outcomes and Effects of Levothyroxine Therapy on Improving Maternal and Infant Prognosis - Chen Li; Xia Li (Clinical and Experimental Obstetrics & Gynecology)
Background: Current evidence shows subclinical hypothyroidism (SCH) is associated with increased risk of adverse pregnancy outcomes, though some controversies exist. However, little is known on the impacts and effectiveness of levothyroxine (LT4) therapy on pregnancy outcomes in women with SCH. Present study aims to investigate the associations between SCH and adverse pregnancy outcomes and clinical effects of levothyroxine (LT4) replacement therapy in patients with SCH. Methods: The clinical data of pregnant women (n = 635) with SCH who referred to Huai'an Maternal and Child Health Care Hospital, Huaian, China from June 2018 to December 2018 were retrospectively analyzed. Among them, 147 cases received standard thyroxine replacement therapy, 292 cases did not receive treatment and 150 cases who received irregular treatment or did not achieve the target or were lost to follow-up. 46 cases whose thyroid peroxidase antibody (TPOAb) was not checked during pregnancy were not included in the study. According to the TPOAb test results patients were divided into positive treatment (n = 14), negative treatment (n = 133), positive untreated (n = 19), or negative untreated (n = 273) subgroups. A total of 1876 pregnant women with normal thyroid function (TPOAb positive = 59; TPOAb negative = 1817) who delivered during the same period were selected as the control group. Pregnancy outcomes were assessed and compared between treated and control group, untreated and control group, TPOAb positive treatment subgroup and TPOAb positive and untreated subgroup, TPOAb negative treatment subgroup and TPOAb negative subgroup, and TPOAb positive and TPOAb negative subgroup. Results: Our data showed that the incidences of hypertensive disease, premature delivery, fetal growth restriction and fetal death during pregnancy in the untreated group were significantly higher than in the control group (p < 0.05). The incidence of preterm delivery in the treatment group was significantly lower compared to the untreated group and the control group (p < 0.05). Moreover, the incidence of premature birth in TPOAb positive treatment subgroup was significantly lower than their peers in TPOAb positive and untreated subgroup. The incidence of premature delivery in TPOAb negative treatment subgroup was significantly lower than TPOAb negative untreated subgroup and the difference was statistically significant (p < 0.05). There was no significant difference in the incidence of adverse pregnancy outcomes between TPOAb positive subgroup and TPOAb negative subgroup in the control group (p > 0.05). Conclusions: SCH during pregnancy is a risk factor for hypertensive disease during pregnancy, fetal growth restriction, premature delivery and fetal death. L-T4 replacement therapy improves maternal and infant outcomes in patients with SCH during pregnancy, regardless of whether or not TPOAb is positive.